2015
DOI: 10.1001/jama.2015.6154
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy vs Appendectomy for Treatment of Uncomplicated Acute Appendicitis

Abstract: IMPORTANCE An increasing amount of evidence supports the use of antibiotics instead of surgery for treating patients with uncomplicated acute appendicitis. OBJECTIVE To compare antibiotic therapy with appendectomy in the treatment of uncomplicated acute appendicitis confirmed by computed tomography (CT). DESIGN, SETTING, AND PARTICIPANTS The Appendicitis Acuta (APPAC) multicenter, open-label, noninferiority randomized clinical trial was conducted from November 2009 until June 2012 in Finland. The trial enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
694
4
22

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(782 citation statements)
references
References 35 publications
23
694
4
22
Order By: Relevance
“…The higher rate of acute relapse in the AP-PAC study might be due to the inclusion of patients with appendicoliths. In a recently published pediatric study, the recurrence rate was found to be 5.3% for patients with appendicoliths and 0% for patients without appendicoliths (31).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The higher rate of acute relapse in the AP-PAC study might be due to the inclusion of patients with appendicoliths. In a recently published pediatric study, the recurrence rate was found to be 5.3% for patients with appendicoliths and 0% for patients without appendicoliths (31).…”
Section: Discussionmentioning
confidence: 94%
“…However, during follow-up of SA, even with a colonoscopy, diagnosis of an underlying tumor or inflammatory bowel disease may still be problematic, and imaging may be required. It has been reported that in conditions in which therapeutic alternatives to surgery are favored, patient satisfaction might be also problematic during follow-up (31). When considering these facts and patient satisfaction during follow-up, imaging may become critical.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the American College of Surgeons performed collective review on 6 key prospective randomized trials of antibiotic therapy vs. appendectomy in non-pregnant adults and concluded that antibiotic therapy is safe for approximately "3 out of 4 adults" [23, [113][114][115][116][117][118]. One of the most compelling studies showed 91% efficacy of antibiotics alone with a 14% rate of recurrent appendicitis at 1 year, but it excluded populations (children and elderly) at high risk of perforation [114].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography of the pediatric gastrointestinal tract can result in morbidity from an associated complication such as appendiceal rupture or bowel obstruction [53,54] . Non-operative management of acute uncomplicated appendicitis in children is also used in select cases [55,56] . Symptoms of acute appendicitis are variable and can include periumbilical and/or right lower quadrant pain, anorexia, nausea, fever, and leukocytosis [54,57] .…”
Section: A B C Dmentioning
confidence: 99%